Copper‐Free Sonogashira Coupling for High‐Surface‐Area Conjugated Microporous Poly(aryleneethynylene) Networks. Issue 21 (15th April 2016) - Trunk, Matthias; Herrmann, Anna; Bildirir, Hakan; Yassin, Ali; Schmidt, Johannes; Thomas, Arne
Abstract: A modified one‐pot Sonogashira cross‐coupling reaction based on a copper‐free methodology has been applied for the synthesis of conjugated microporous poly(aryleneethynylene) networks (CMPs) from readily available iodoarylenes and 1, 3, 5‐triethynylbenzene. The polymerization reactions were carried out by using equimolar amounts of halogen and terminal alkyne moieties with extremely small loadings of palladium catalyst as low as 0.65 mol %. For the first time, CMPs with rigorously controlled structures were obtained without any indications of side reactions, as proven by FTIR and solid‐state NMR spectroscopy, while showing Brunauer–Emmett–Teller (BET) surface areas higher than any poly(aryleneethynylene) network reported before, reaching up to 2552 m 2 g −1 . Abstract : A modified one‐pot Sonogashira cross‐coupling reaction based on a copper‐free methodology has been applied for the synthesis of conjugated microporous polymers (CMPs). Not only are the resulting structures much more defined than previously published materials, but they also show far superior Brunauer–Emmett–Teller (BET) surface areas of up to 2552 m 2 g −1, setting a new record for this type of materials (see scheme).